In Vitro Comparison of Apical Leakage in Root Canals Obturated with 0.04 and 0.02 Tapered Gutta-Percha - Bidar, Maryam; Sadeghi, Ghazal; Gharechahi, Maryam; Mortazavi, Mohammad; Forghani, Maryam (Iranian Endodontic Journal, 2010)
INTRODUCTION: Gutta-percha is the most commonly used material for root canal obturation; it has been recently manufactured with different tapers. The aim of this in vitro study was to compare microleakage of canals obturated with standard gutta-percha (0.02 taper) or the new 0.04 taper gutta-percha master cone using the cold lateral condensation technique. MATERIALS AND METHODS: Forty-four extracted single rooted teeth were selected. The crowns were removed and all the canals were prepared using RaCe rotary files. The teeth were then divided into experimental (n=2) and control (n=2) groups. In the first study group, the teeth were obturated with 0.02 taper gutta-percha master cone and lateral condensation. In the second study group, the canals were obturated by 0.04 tapered master cones and the same obturation method. The degree of leakage was measured using fluid filtration method. Data were analyzed statistically by student t-test. RESULTS: There was no significant difference between the mean microleakage of two experimental groups (P=0.558). CONCLUSION: Lateral condensation technique using 0.04 tapered master cones can provide an effective apical seal similar to 0.02 gutta-percha cones.